Russian peasant letters : texts and contexts - Yokoyama, Olga Tsuneko (Harrassowitz Verlag, 2014)
Around 1880, two teenagers left their village on the Kama river, 1000 km east of Moscow. Their father wanted them to earn cash in Siberia and send it home. The result: scores of letters over a period of 16 years (1881-1896). The parents, two brothers and a sister reported on harvests and family finances, on marriages, births, and deaths, asked for money, offered religious instruction and moral advice, described their daily lives, and shared their worries about their alcoholic father and their desire to see the world and succeed in it. Meanwhile, the family's activity steadily expanded, as thei.